Character education in learning history of the Diponegoro war material - Afriani, Yesti; Agustiningsih, Nur; Karmela, Siti Heidy (Journal of Research in Instructional, 2022)
This study aims (1) to determine the readiness of teachers to carry out character education in learning the history of the material "Diponegoro war" in class XI at a high school in the Sarolangun area, Jambi Province, (2) To determine the character values ​​contained in the material for the Diponegoro war class XI and (3) To find out the implementation of the implementation of character education in learning the history of the material "Diponegoro war. The researcher uses a descriptive type of research. Data collection techniques used by researchers are observation, interviews and documentation. Meanwhile, the data analysis technique is by reducing the data, presenting the data and concluding it. From the results of the research and discussion, it was found that the preparation that the History teacher had to do in the implementation of learning the history of the Diponegoro war material with character education in it was the lesson plan that was in accordance with the syllabus, Curriculum 13, and also the material included in the learning indicators. Furthermore, several good and bad characters were found during the historical study of the Diponegoro war. These characters are religious, honest, tolerant, democratic, love the homeland, discipline, social care, self-confidence and responsibility. While the bad character is lying, rebellious, disobedient to the rules, lazy, traitor and selfish. Good characters are used as role models in history learning, and bad characters should be avoided. Finally, the implementation of character education in history learning in the Diponegoro war material went well through the stages of giving examples or examples, spontaneous activities, reprimands, conditioning the school atmosphere and routine activities.